Benchmarking and productivity analysis in South Africa's automotive industry - Moshikaro, Lesego (School of Economics, 2021)
Despite being the biggest beneficiary of industrial policy, South Africa's automotive industry has struggled to remain competitive relative to its peers. This is partly a result of increasing global competition, structural shifts and changing demand. At the same time, the local industry remains constrained by a slowdown in economic growth, increasing labour costs and insufficient economies of scale. By analysing the role of policy in improving competitiveness and export performance in South Africa's automotive industry, this paper provides an overview of driving forces, challenges and trends in the local industry. The study uses benchmarking data to analyse productivity improvements in the industry. It finds that South African component firms have implemented lean and world class production techniques, improving their operational competitiveness with significant improvements in quality, inventory reduction and delivery reliability to customers. Although South Africa appears to be catching-up to its competitors, it still ranks poorly among auto-producers in emerging markets. Its competitors in the Far East, South America and Eastern Europe enjoy low production costs, rising FDI inflows and proximity to end markets. Policy interventions influence competitive advantages. This therefore highlights the important role of government in developing a policy mix that aims to increase firm-level competitiveness through minimising operational costs, improving production flexibility and encouraging higher local content to foster industrial development.